(untitled) (Innovative professional education, 2025)
Based on the analysis of various digital platforms for hosting and further using electronic manuals, methodological recommendations have been provided on the optimal sequence of actions to meet the educational needs of students. Modern educational digital platforms play a key role in training specialists in vocational education institutions, especially in colleges. When registering users on such platforms, it is necessary to ensure a high level of security and confidentiality of data, since students provide personal and academic information. Modern encryption methods, two-factor authentication, and password protection are mandatory to prevent data leakage. An important aspect is informing users about their rights and obligations regarding processing personal data. The training of specialists who develop and support educational resources should include knowledge of cybersecurity and compliance with international standards.